Analysis of Local Government Strategies in Capacity Building for Regional Financial, Asset, and Revenue Management Bodies in Baubau City, Indonesia - Herman Lawealai; Nastia; Hastuti (International Journal of Science, Technology & Management, 2021)
This study aims to analyze strategies for increasing the capacity of the Regional Financial, Asset, and Revenue Management Bodies in the City of Baubau. Clarity regarding where the local government is as a developed institution. The district/city policy strategy as a region and institution has not been formulated in a clear and clear manner. Even though the government has clearly been given the authority to formulate a strategy for the creation of a strategic public service policy to the public. This research study uses a SWOT analysis technique with a qualitative approach, which consists of Strengths, Weaknesses, Opportunities, and Threats. SWOT analysis aims to maximize strengths and opportunities but can minimize weaknesses and threats.By evaluating internal factors including the strength of the Baubau City Finance, Asset, and Regional Revenue Management Agency in increasing organizational capacity; Weaknesses, namely all factors that are not beneficial or detrimental to the Regional Financial, Asset and Income Management Agency of Baubau City. Meanwhile, evaluation of external factors includes opportunities, namely all the opportunities that exist as government policies, applicable regulations or national or global economic conditions which are considered to provide opportunities for capacity building to grow and develop in the future; Threats, namely things that can cause losses to the capacity building of the Baubau City Financial Management Agency, Asset, and Regional Revenue. The results of this study indicate that there are 4 alternative strategies obtained from compiling a SWOT matrix derived from the identification of internal and external factors in order to improve the service performance of the Financial Management Agency, Asset and Regional Income of Baubau City. The alternative strategies are the Strength-Opportunity (S-O) Strategy, the Weakness-Opportunity (W-O) Strategy, the Strength-Threat (ST) Strategy, and the Weakness-Threat (WT) Strategy.